Transport Variability in the Lanzarote Passage (Eastern Boundary Current of the North Atlantic Subtropical Gyre) - Hernández-Guerra, Alonso; Fraile-Nuez, Eugenio; Borges, R.; López-Laatzen, Federico; Vélez-Belchí, Pedro; Parrilla-Barrera, Gregorio; Müller, T.J. (Deep Sea Research Part I: Oceanographic Research Papers, 2003)
Observations from a four-year current meter mooring at 28°44′N, 13°28′W in the Lanzarote passage are used to describe the transport variability of the Eastern Boundary Current of the North Atlantic Subtropical Gyre. Three different water masses are found in the passage: North Atlantic Central Water in the upper levels (roughly ), Antarctic Intermediate Water (roughly ) and Mediterranean Water in the layer above the bottom at . The mean southward transport of NACW is which is the transport of the easternmost branch of the Canary Current. Fluctuations of NACW transport are large, ranging from southward to northward. Every autumn a consistent northward transport is observed, which may be related with the eastern boundary upwelling dynamics. The mean transports of AAIW and MW are northward and southward, respectively. Fluctuations of transport of AAIW and MW are large, from 1.0 to and from −0.32 to , respectively. Thus, the mass transports for each water mass show a high standard deviation of comparable magnitude to the mean. This highlights the importance of the temporal variability of the currents in this passage. A remarkable feature of our observations is that the mean transports of NACW and AAIW during an El Niño event are significantly different. No